Nazi Germany : A Very Short Introduction - Caplan, Jane (New York Oxford University Press, 2019)
The Nazi regime dominated European history for twelve years between 1933 and 1945, and left a legacy that still echoes today. Nazi Germany: A Very Short Introduction provides a highly relevant reminder of the fragility of democratic institutions, and the ways in which a mass political movement, the exploitation of popular fears, and frail political opposition can lead to the imposition of dictatorship. After considering the emergence and popular appeal of the Nazi party, it examines the relationships between belief, consent, and terror in securing the regime, alongside the crucial role played by Hitler. Arguing that war and conquest were intrinsic to National Socialism, this VSI shows how genocide became its ultimate goal, and concludes with a discussion of the place of Nazi Germany in history and public memory.
Include References and Index
Keywords: Germany -- National socialism